Closing the gap: artificial intelligence applied to ultrasound-guided regional anaesthesia. (March 2023) - Hewson, David W.; Bedforth, Nigel M.
Summary: The role of artificial intelligence in ultrasound-guided regional anaesthesia is explored in a recent study by Bowness and colleagues, published in the British Journal of Anaesthesia . The investigators showed that non-expert ability to identify key sono-anatomical structures was improved with the assistance of proprietary artificial intelligence software. Whether such software could increase learning efficiency, and thereby patient access, to regional anaesthesia, will require further study.